Challenges for the immunoglobulin and T cell receptor gene nomenclatures in the modern genomics era - Andrew M. Collins; Corey T. Watson; Henk-Jan van den Ham; Luc Teyton; Elisa Rosati; Yana Safonova (ImmunoInformatics, 2025)
For over thirty years, an approach to the nomenclatures of human immunoglobulin (IG) and T cell receptor (TR) genes has operated successfully and has been widely supported by the research community. The principles behind the human nomenclatures were then applied to the development of nomenclatures for IG and TR genes in non-human species. More recently, however, genomic sequencing has highlighted the limitations of this historic approach to nomenclature. The sequencing of IG and TR gene loci from multiple individuals and from a number of species has unveiled an extraordinary level of structural variation within the loci of all species that have so far been studied in this way. The designated gene naming authority - the International Union of Immunological Societies (IUIS) IG and TR Nomenclature Sub-Committee - has determined that a more careful approach is required before the genes of any species are officially named. In this opinion piece, we outline the challenges of the IG and TR nomenclatures, hoping to stimulate dialogue within the research community. Such dialogue would help guide the formulation of official policies to determine the appropriate level of knowledge of a locus that should be required before official gene names can be assigned. Strategies are also presented that should allow the unambiguous reporting and discussion of IG and TR gene sequences if their official naming is delayed.